Highly Solvent Tolerance in Serratia marcescens IBBPo15 - Stancu,Mihaela Marilena (2016)
ABSTRACT The aim of this study was to investigate the solvent tolerance mechanisms in Serratia marcescens strain IBBPo15 (KT315653). Serratia marcescens IBBPo15 exhibited remarkable solvent-tolerance, being able to survive in the presence of high concentrations (above 40%) of toxic organic solvents, such as cyclohexane, n-hexane, n-decane, toluene, styrene, and ethylbenzene. S. marcescens IBBPo15 produced extracellular protease and the enzyme production decreased in cells exposed to 5% cyclohexane, n-hexane, toluene, styrene, and ethylbenzene, as compared with the control and n-decane exposed cells. S. marcescens IBBPo15 cells produced carotenoid pigments and alteration of pigments profile (i.e., phytoene, lycopene) were observed in cells exposed to 5% cyclohexane, n-hexane, n-decane, toluene, styrene, and ethylbenzene. The exposure of S. marcescens IBBPo15 cells to 5% cyclohexane, n-hexane, n-decane, toluene, styrene, ethylbenzene induced also changes in the intracellular (e.g., 50 kDa protein) and extracellular (e.g., 39, 41, 43, 53, 110 kDa proteins) proteins profile. Significant RAPD, ARDRA, rep-PCR and PCR pattern modifications were not observed in DNA extracted from S. marcescens IBBPo15 cells exposed to 5% cyclohexane, n-hexane, n-decane, toluene, styrene, and ethylbenzene. Though only HAE1 and acrAB genes were detected in the genome of S. marcescens IBBPo15 cells, the unspecific amplification of other fragments being observed also when the primers for ompF and recA genes were used.